2012
DOI: 10.1021/jp306917x
|View full text |Cite
|
Sign up to set email alerts
|

Guest–Host Interactions Investigated by Time-Resolved X-ray Spectroscopies and Scattering at MHz Rates: Solvation Dynamics and Photoinduced Spin Transition in Aqueous Fe(bipy)32+

Abstract: We have studied the photoinduced low spin (LS) to high spin (HS) conversion of [Fe(bipy)(3)](2+) in aqueous solution. In a laser pump/X-ray probe synchrotron setup permitting simultaneous, time-resolved X-ray diffuse scattering (XDS) and X-ray spectroscopic measurements at a 3.26 MHz repetition rate, we observed the interplay between intramolecular dynamics and the intermolecular caging solvent response with better than 100 ps time resolution. On this time scale, the initial ultrafast spin transition and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
189
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(206 citation statements)
references
References 62 publications
15
189
2
Order By: Relevance
“…The advantages of using hard X-rays will allow us to use this technique to study materials in situ under extreme conditions, or during chemical transformations, even on the ultrafast time scale (fs or ps). The application of (core-tocore) XES as a probe in ultrafast pump-and-probe experiments has commenced 69,72,73 , however, the chemical sensitivity of valence-to-core emission spectroscopy is expected to lead to milestones in the deeper understanding of the elementary steps of ultrafast processes. This includes photochemical transitions of Br-bearing compounds, for which time-resolved XAS and X-ray scattering investigations have already started 67,68 .…”
Section: Theoretical Modelling Of the Xes Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of using hard X-rays will allow us to use this technique to study materials in situ under extreme conditions, or during chemical transformations, even on the ultrafast time scale (fs or ps). The application of (core-tocore) XES as a probe in ultrafast pump-and-probe experiments has commenced 69,72,73 , however, the chemical sensitivity of valence-to-core emission spectroscopy is expected to lead to milestones in the deeper understanding of the elementary steps of ultrafast processes. This includes photochemical transitions of Br-bearing compounds, for which time-resolved XAS and X-ray scattering investigations have already started 67,68 .…”
Section: Theoretical Modelling Of the Xes Spectramentioning
confidence: 99%
“…While such measurements might not be of utmost importance in static experiments because of the availability of other and simpler techniques, studying ultrafast processes, for instance, photodissociation or photolysis of Br-bearing systems [66][67][68] , could benefit from a novel timeresolved tool. Such processes have already been investigated by time-resolved XAS and X-ray scattering 67,68 , however, recent works on other systems have demonstrated that XES, especially when combined with these other tools, can lead to a better understanding of the molecular transformations and the nature of the intermediates in ultrafast pump-probe experiments [69][70][71][72][73] . Our main motivation was to find out which of the 1s emission lines offer sufficient chemical sensitivity for such studies.…”
Section: Introductionmentioning
confidence: 99%
“…[49] This agrees with recent time-resolved X-ray experiments on Fe(bpy) 3 complexes in which it was found that upon excitation the number of water moleculesreducesbytwoonthepicosecond time scale. [50] Corresponding simulations for the Fe-complex, also using the VA L-BOND-Trans (VBT) force field, confirm this finding. [51] The simulations employ the VBT force field [52] which is an extension of the VA LBOND force field.…”
Section: Solvation Dynamicsmentioning
confidence: 65%
“…This article concerns the analysis of a set of data from an experiment carried out at the XPP end station at the LCLS using the first version of the CS-PAD detector to be installed there. The scientific goal of these experiments was to investigate the interplay between electronic and structural dynamics in the spin crossover compound [Fe(bpy) 3 ] 2þ in aqueous solution by using simultaneous, time-resolved (TR) X-ray emission spectroscopy and X-ray scattering as in recent synchrotron experiments [10]. The scientific results of the new XFEL investigations are presented in [11].…”
Section: Introductionmentioning
confidence: 99%